2016
DOI: 10.1016/j.marpolbul.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Wave energy level and geographic setting correlate with Florida beach water quality

Abstract: Many recreational beaches suffer from elevated levels of microorganisms, resulting in beach advisories and closures due to lack of compliance with Environmental Protection Agency guidelines. We conducted the first statewide beach water quality assessment by analyzing decadal records of fecal indicator bacteria (enterococci and fecal coliform) levels at 262 Florida beaches. The objectives were to depict synoptic patterns of beach water quality exceedance along the entire Florida shoreline and to evaluate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…Results from the present study show that beach type is highly associated with exceedance levels, which is consistent with the prior study that found associations between wave energy and FIB exceedance levels (Feng et al 2016). In this study, we categorized the beaches based on geomorphology and found that open coast beaches had the lowest average exceedance, whereas bay beaches had, on average, 4 times the exceedance relative to category 1 beaches.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Results from the present study show that beach type is highly associated with exceedance levels, which is consistent with the prior study that found associations between wave energy and FIB exceedance levels (Feng et al 2016). In this study, we categorized the beaches based on geomorphology and found that open coast beaches had the lowest average exceedance, whereas bay beaches had, on average, 4 times the exceedance relative to category 1 beaches.…”
Section: Discussionsupporting
confidence: 92%
“…They also receive a considerable amount of river and canal input as water is brought to the ocean. Marsh beaches, although not behind barrier islands, are characterized by extremely shallow bottom slopes (Feng et al 2016) and the presence of surrounding wetland areas. It is possible that marsh areas are characterized by different water chemistry and more highly organic coastal sediments that may play a role in the elevation of enterococci.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations